2021
DOI: 10.1136/jitc-2021-003675
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell vaccines targeting tumor blood vessel antigens in combination with dasatinib induce therapeutic immune responses in patients with checkpoint-refractory advanced melanoma

Abstract: BackgroundA first-in-human, randomized pilot phase II clinical trial combining vaccines targeting overexpressed, non-mutated tumor blood vessel antigens (TBVA) and tyrosine kinase inhibitor dasatinib was conducted in human leukocyte antigen (HLA)-A2+ patients with advanced melanoma.MethodsPatient monocyte-derived type-1-polarized dendritic cells were loaded with HLA-A2-presented peptides derived from TBVA (DLK1, EphA2, HBB, NRP1, RGS5, TEM1) and injected intradermally as a vaccine into the upper extremities ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Despite the limited success of exploratory therapies, a slew of additional treatment mechanisms are being studied in ongoing trials and may pique the interest of patients and clinicians when approved therapies are not an option. Dendritic cell vaccine therapies, for example, have shown promise in phase 2 trials and continue on in phase 3 [ 51 ]. VEGFR blockers which are efficacious for other cancers [ 52 ] also show promising results in early phase trials in melanoma [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limited success of exploratory therapies, a slew of additional treatment mechanisms are being studied in ongoing trials and may pique the interest of patients and clinicians when approved therapies are not an option. Dendritic cell vaccine therapies, for example, have shown promise in phase 2 trials and continue on in phase 3 [ 51 ]. VEGFR blockers which are efficacious for other cancers [ 52 ] also show promising results in early phase trials in melanoma [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been suggested to affect immunotherapy by tumor cell anaerobic glycolysis; the metabolite adenosine secreted to the ECM suppressed T cell activation, and thus, excused the tumor cells from immune attack ( 25 ), indicating the promising therapeutic strategy developed from cancers with hypoxia. Currently, hypoxia has presented association with immunotherapy response or immune checkpoint effects in many cancers ( 26 28 ), whereas only a clinical trial consisting of mixed melanoma patients suggested that the PD-1 blockage responders of immunotherapy has a reduced hypoxia transcriptomic change ( 29 ). In this study, we observed many upregulated immune checkpoints in the high-risk group and C1 subtype and transcription similarity with the samples that responded to the PD-1 therapy, demonstrating the potential of hypoxia as the target to improve immunotherapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our study further highlights the role of B cells in ovarian cancer biology as shown by studies in other tumor types [ 35 , 38 , 39 ]. For example, a recent study demonstrated that formation of B cell-rich TLS structures is associated with epitope spreading and predicts the occurrence of clinical responses to DC vaccines in patients with advanced PD1-resistant melanoma [ 40 ]. Additionally, results from studies on humoral immunity in response to vaccines for influenza or COVID-19 in patients with solid tumors treated with cytotoxic therapies also reveal a preserved ability for seroconversion during or after treatment, further highlighting the conserved state of B cell responsiveness during chemotherapy [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%